Recent Advances in Exploration and Biotechnological Production of Bioactive Compounds in Three Cyanobacterial Genera: Nostoc, Lyngbya, and Microcystis - Thuan, Nguyen Huy; An, Tran Tuan; Shrestha, Anil; Canh, Nguyen Xuan; Sohng, Jae Kyung; Dhakal, Dipesh (Frontiers in Chemistry, 2019)
Cyanobacterias, are only Gram-negative bacterias with oxygenic photosynthetic capability, so termed as “Cyanophyta” or “blue-green algae”. They occur ubiquitously in diverse environments such as soil, water, rock and other organisms (symbiosis, commensalism or parasitism, etc). They have been characterized as prominent producer of numerous types of important compounds with anti-microbial, anti-viral, anti-inflammatory and anti-tumor properties. Among the cyanobacterial genus, members belonging to genus Nostoc, Lyngbya, and Microcystis have attained greater attention. The major reason for it is that the strains belonging to these genus are most prominent producer of compounds with diverse activities/structures, including compounds in preclinical and/or clinical trials (cryptophycin and curacin), or compounds having unique activities as protease inhibitor (micropeptins and aeruginosins). Most of these compounds have been tested for their efficacy and mechanism of action through in vitro and/or in vivo studies. Recently, advances in culture techniques of these cyanobacteria, and isolation, purification, and chromatographic analysis of their compounds have revealed insurmountable novel bioactive compounds from these cyanobacterias. This review provides updates in the origin, isolation and purification methods, chemical structures and biological activities of the major compounds from Nostoc, Lyngbya, and Microcystis. In addition, multi-omics approaches and biotechnological production of compounds from selected cyanobacterial genera have been presented.